Endothelial ENaC as a repressor of oxidative stress and a guardian of lung capillary barrier function in bacterial and viral pneumonia - Eaton, D. C.; Romero, M. J.; Matthay, M. A.; Hamacher, J.; Advani, A.; Wolf, A.; Abu Mraheil, M.; Chakraborty, T.; Stepp, D. W.; Belin de Chantemèle, E. J.; Kutlar, A.; Kraft, F.; et al. (Frontiers in Physiology, 2025)
The endothelium represents a crucial regulator of vascular homeostasis. Since endothelial cells mainly rely on glycolysis rather than on oxidative phosphorylation for their ATP generation, this allows capillaries to transport the maximum amount of oxygen to oxygen-starved tissues, where it can be used for energy generation. However, the occasionally high levels of oxygen and of reactive oxygen species (ROS) in the blood vessels requires a balancing act between pro- and anti-oxidative mechanisms in the endothelium. When this balance is disturbed by excessive oxidative stress, as can occur in bacterial and viral pneumonia, endothelial barrier function can be compromised. This review will discuss some of the recently discovered barrier-protective mechanisms during bacterial and viral pneumonia, mediated through the reduction of oxidative stress in lung capillaries by the epithelial sodium channel (ENaC).